The relationship of preoperative and postoperative serum CEA and CA 19-9 levels with tumor localization, stage and overall survival in patients with colorectal cancer (Annals of Medical Research, 2021)
Aim: To evaluate the prognostic value of pre/postoperative serum levels of Carcinoembryonic antigen (CEA), Carbohydrate antigen 19-9 (CA 19-9), and their relationship with primary localization and stage of colorectal cancer (CRC) patients. Materials and Methods: 255 patients who underwent curative or palliative surgery with the diagnosis of CRC between 2015 and 2020 were included in the study. The patients were divided into groups as right colon tumor and left colon tumor based on the region of the primary tumor. Baseline data on age, sex, location of primary tumor, disease stage, histological differentiation, BRAF and RAS mutation situations and serum CEA and CA 19-9 levels were recorded before and after surgery. Individuals were followed for at least sixty months or until they died. Overall survival (OS) and Disease Free Survival (DFS) rates were estimated using the Kaplan–Meier method.Results: 103 patients had right sided (41.4%) and 152 patients (59.6%) had left sided CRC. Most of the patients were in the early stage (71%). DFS and OS patients with left colon tumors were longer than the right. [(DFS, 32.18 (6-60) vs. 34.25 (6-60) months, p=0.332) and (OS, 41.16 (6-60) vs. 49.05 (11-60) months, p=0.002]. An assessment of the prognosis showed that the OS was significantly worse in the patients with a high CEA level (p=0.001) and in the patients with a high CA 19-9 level (p=0.001). In multivariate analysis, normal serum CA 19-9 levels (p=0.002), RAS wild type tumor (p0.001), early stage disease (p=0.004) were identified as a good prognostic factors for OS of these patients.Conclusion: It was determined that left colon tumors had a longer life span than right side. Elevated levels of CEA and CA 19-9 pre and postoperative in CRC have a worst prognosis than those with normal levels of these markers.
Keywords: CA 19-9; CEA; colorectal cancer; tumor localization; stage; survival